2021
DOI: 10.1371/journal.pone.0260825
|View full text |Cite
|
Sign up to set email alerts
|

Acute and delayed effects of strength training in ball velocity and accuracy in young competition tennis players

Abstract: This study aimed to investigate the acute and delayed effects of medicine ball throws and resistance training in ball velocity and accuracy of serve, forehand and backhand in young competition tennis players. A crossover-randomized design was used with 10 competition tennis players (6 girls and 4 boys between 14 and 18 years old). The subjects performed 6 stroke test sessions, 3 for each strength protocol. The velocity and accuracy of strokes were measured before (basal situation), 3 minutes, 24 and 48 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
(58 reference statements)
0
4
0
2
Order By: Relevance
“…Maquirrain et al (2016) and Moreno-Pérez et al 30 did not observe reductions in precision or speed of elite tennis players after 5-set matches. On the contrary, studies have found reductions in SV (3.9%-4%) in competition players of lower level [49][50][51][52] or age, 53 suggesting experienced athletes could be able to find strategies to avoid the reduction of SV in fatiguing situations. Nevertheless, investigations are limited when examining the influence of fatigue on SV in young competitors, making of great interest further studies on the topic.…”
Section: Factors Negatively Affecting Svmentioning
confidence: 93%
See 1 more Smart Citation
“…Maquirrain et al (2016) and Moreno-Pérez et al 30 did not observe reductions in precision or speed of elite tennis players after 5-set matches. On the contrary, studies have found reductions in SV (3.9%-4%) in competition players of lower level [49][50][51][52] or age, 53 suggesting experienced athletes could be able to find strategies to avoid the reduction of SV in fatiguing situations. Nevertheless, investigations are limited when examining the influence of fatigue on SV in young competitors, making of great interest further studies on the topic.…”
Section: Factors Negatively Affecting Svmentioning
confidence: 93%
“…47 Notwithstanding, this fatigue does not seem to affect all players in the same way and is most likely determined by match load, experience, and playing level. Terraza and Baiget 50 found no reductions in accuracy or SV following a resistance training or MBT protocol, suggesting although impairments could have appeared in strength and power levels, players may rely on different neuromuscular parameters to maintain performance during the serve. Maquirrain et al (2016) and Moreno-Pérez et al 30 did not observe reductions in precision or speed of elite tennis players after 5-set matches.…”
Section: Factors Negatively Affecting Svmentioning
confidence: 98%
“…Quality ball placement and speed of the stroke are essential for attaining the best performance, and therefore their assessment is really important for the overall quality of the stroke (Terraza-Rebollo & Baiget, 2021). In addition to performing a stroke quickly and with precision, maintaining a high percentage of placing strokes into the field, during intensive periods in a match, presents a key component for winning in modern-day fast-paced tennis (Kovacs, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…I (2023) 55-70, ISSN: 2952-2218 aumento de la conciencia articular y la propiocepción general (Pardos-Mainer et al, 2020). Por otro lado, se evalúa la relación velocidad-carga mediante el press banca, cuya mejora en los deportes explosivos como el tenis y la pelota genera resultados positivos en la potencia de golpeo de la pelota al aumentar el tamaño del músculo y las fibras musculares de tipo IIx (Terraza-Rebollo & Baiget, 2021).…”
Section: Introductionunclassified
“…En la literatura científica no existen estudios sobre el entrenamiento de fuerza basados en la velocidad de ejecución en jugadores pelotaris de alto rendimiento, pero sí en otros deportes con ciertas similitudes como es el fútbol, tenis o baloncesto (Pardos-Mainer et al, 2017Terraza-Rebollo & Baiget, 2021). En alto rendimiento, lo habitual es ver planificaciones realizadas en base a la velocidad de ejecución y trabajar con cargas medias sin llegar nunca al fallo.…”
Section: Introductionunclassified